First case report of infection caused by Encephalitozoon intestinalis in a domestic cat and a patient with AIDS - Velásquez, Jorge Néstor (2012)
Microsporidia are eukaryotic, intracellular obligate parasites that infect invertebrate and vertebrate animals, and have emerged as important opportunistic parasites in AIDS patients. We used light microscopy to detect microsporidial spores in stool samples of a domestic cat confirmed as Encephalitozoon intestinalis by PCR, owned by an AIDS patient with chronic diarrhea and E. intestinalis infection. Cats can be considered hosts of E. intestinalis.